2022
DOI: 10.14309/crj.0000000000000941
|View full text |Cite
|
Sign up to set email alerts
|

Turmeric-Associated Drug-Induced Liver Injury

Abstract: Turmeric is a common herbal supplement used for its possible anti-inflammatory and other properties. It is marketed as safe with few reports of major adverse effects directly related to oral supplementation. We report a case of turmeric supplement-induced liver injury in a 49-year-old woman admitted with elevated aspartate aminotransferase and alanine aminotransferase with no history of liver disease or alcohol use disorder. Thus, this case re-emphasizes the importance of evaluating herbal and dietary suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…The authors reported the cases had RUCAM scores of 7 and 6, respectively. Another recent turmeric and piperine supplement-induced liver injury case was reported in a 49-year-old woman admitted with elevated aspartate aminotransferase and alanine aminotransferase with no history of liver disease [43]. The authors sent the supplement for mass spectrometry analysis, which confirmed the curcumin component, albeit less than the label-reported amount.…”
Section: Turmeric/curcuminmentioning
confidence: 91%
“…The authors reported the cases had RUCAM scores of 7 and 6, respectively. Another recent turmeric and piperine supplement-induced liver injury case was reported in a 49-year-old woman admitted with elevated aspartate aminotransferase and alanine aminotransferase with no history of liver disease [43]. The authors sent the supplement for mass spectrometry analysis, which confirmed the curcumin component, albeit less than the label-reported amount.…”
Section: Turmeric/curcuminmentioning
confidence: 91%